Contributions of Behavior Analysis to the study of the phehomenon of xenophobia: a literature review - Ijanc Neto, Conrado E.; Picoli, Aline; Aggio, Natália M. (Perspectivas em Análise do Comportamento, 2022)
The refugees crisis is an issue of great social relevance, which in turn, is followed by a discussion about behaviors related to rejection towards foreigners, named as xenophobia. Given the importance of this theme, along with the perspective of the potential of behavior analysts debates for social issues solving, the purpose of this study was to perform a literature review about xenophobia, covering published papers whose theoretical reference was supported in Behavior Analysis. The search was conducted through the keywords “xenophobia”, “refugees” or “terrorism”, in April 2021, on PsycINFO APA database and in seven national and international Behavior Analysis journals. The results led to seven papers, all published in English between 1991 and 2019. Five of them consisted in empirical studies, whereas the other two presented theoretical contributions. It is outstanding that most part of these papers investigate the prejudice against Middle East people, under the argument that, from the September 11 Attacks on, the rejection of North Americans population towards this people has increased. Despite its urgency, no applied research on this topic was found among the aforementioned studies, and all of the empirical ones were based in the conflicting relations paradigm.